1999
DOI: 10.1038/13014
|View full text |Cite
|
Sign up to set email alerts
|

The dynamin-related GTPase Dnm1 regulates mitochondrial fission in yeast

Abstract: The dynamin-related GTPase Dnm1 controls mitochondrial morphology in yeast. Here we show that dnm1 mutations convert the mitochondrial compartment into a planar 'net' of interconnected tubules. We propose that this net morphology results from a defect in mitochondrial fission. Immunogold labelling localizes Dnm1 to the cytoplasmic face of constricted mitochondrial tubules that appear to be dividing and to the ends of mitochondrial tubules that appear to have recently completed division. The activity of Dnm1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
643
0
8

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 698 publications
(703 citation statements)
references
References 21 publications
42
643
0
8
Order By: Relevance
“…In yeast, selective inhibition of either processes significantly modifies mitochondrial size and interconnectivity [23,24]. Among the best-known proteins involved in mitochondrial dynamics are Fzo/mitofusin, a transmembrane GTPase involved in fusion [25], and Dnm1p/dynamin-related protein 1, a dynamin-related protein involved in fission [26].…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, selective inhibition of either processes significantly modifies mitochondrial size and interconnectivity [23,24]. Among the best-known proteins involved in mitochondrial dynamics are Fzo/mitofusin, a transmembrane GTPase involved in fusion [25], and Dnm1p/dynamin-related protein 1, a dynamin-related protein involved in fission [26].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies (described above) suggested that loss of Dnm1p function blocked mitochondrial fission but allowed the fusion of mitochondrial tips to continue, resulting in the formation of elaborate net-like structures [9,10]. Most importantly, the mitochondrial fragmentation induced by a fzo1 mutation no longer occurred in cells containing a dnm1 mutation [9,10].…”
Section: Fission and The Outer Membrane Gtpase Dnm1pmentioning
confidence: 99%
“…In dnm1 mutant cells, mitochondrial fission is abolished but fusion of mitochondrial tips continues, resulting in the formation of elaborate 'net-like' structures ( Fig. 3, left) [9,10]. By contrast, mitochondrial networks rapidly fragment in fzo1 mutant cells because mitochondrial fusion is blocked but fission continues unopposed (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Drp1/Dnm1, a dynamin-like GTPase, three other proteins were identified in yeast that are required for normal mitochondrial fission, Fis1, Mdv1/ Net2 and Caf4 (Bleazard et al, 1999;Sesaki and Jensen, 1999;Jensen et al, 2000;Shaw and Nunnari, 2002;Griffin et al, 2005). A critical role for each of these factors in yeast mitochondrial fission is evident from the fact that deletion of any one of them results in fusion of normally tubular mitochondria into continuous nets.…”
Section: 'Day Jobs' For Pro-death Mitochondrial Proteinsmentioning
confidence: 99%